2003
DOI: 10.1016/s0092-8674(03)00815-8
|View full text |Cite
|
Sign up to set email alerts
|

The AAA-ATPase Cdc48/p97 Regulates Spindle Disassembly at the End of Mitosis

Abstract: Spindle disassembly at the end of mitosis is a complex and poorly understood process. Here, we report that the AAA-ATPase Cdc48/p97 and its adapters Ufd1-Npl4, which have a well-established role in membrane functions, also regulate spindle disassembly by modulating microtubule dynamics and bundling at the end of mitosis. In the absence of p97-Ufd1-Npl4 function, microtubules in Xenopus egg extracts remain as monopolar spindles attached to condensed chromosomes after Cdc2 kinase activity has returned to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
161
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(171 citation statements)
references
References 58 publications
(4 reference statements)
9
161
1
Order By: Relevance
“…These observations suggest that the CDC-48 UFDϪ1/NPLϪ4 complex is crucial for DNA replication initiation, which might not involve a role in CDT-1 turnover. Several previous studies have described different activities of Cdc48/p97 in mitotic events, such as spindle disassembly and nuclear envelope reformation (6,7,10,11). Here, we identified a role for CDC-48 UFDϪ1/NPLϪ4 in DNA replication, which is important for cell cycle progression (Fig.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…These observations suggest that the CDC-48 UFDϪ1/NPLϪ4 complex is crucial for DNA replication initiation, which might not involve a role in CDT-1 turnover. Several previous studies have described different activities of Cdc48/p97 in mitotic events, such as spindle disassembly and nuclear envelope reformation (6,7,10,11). Here, we identified a role for CDC-48 UFDϪ1/NPLϪ4 in DNA replication, which is important for cell cycle progression (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Early observations in yeast and recent findings using Xenopus egg extracts suggested that Cdc48/p97 regulates spindle disassembly during exit from mitosis (6,7). For example, spindle regulators such as the Polo-like kinase Plx remain attached and probably stabilize the spindle in the absence of p97 Ufd1/Npl4 .…”
mentioning
confidence: 99%
“…In recent studies, the ATPase p97/VCP of the AAA (ATPases associated with diverse cellular activities) family has been implicated in the proteasomal degradation of certain cytosolic substrates (9)(10)(11)(12)(13). VCP is capable of dissociating proteins from large cellular structures such as the endoplasmic reticulum (14), the mitotic spindle (12), the nuclear envelope (15), and chromatin (16).…”
Section: Intracellular Immunity | Cdc48mentioning
confidence: 99%
“…Studies in Xenopus egg extracts have shown that CDC48/p97/VCP-Ufd1-Npl4 complex-mediated disassembly of mitotic spindles is through its interaction with XMAP215 and TPX2 and regulates their binding to microtubules at mitotic exit (6). This regulation is independent of XMAP215 and TPX2 degradation.…”
mentioning
confidence: 99%